Exchange and crystal field effects in the ESR spectra of Eu(2+) in LaB(6) - Duque, J. G. S.; Urbano, R. R.; Venegas, Pablo Antonio [UNESP]; Pagliuso, P. G.; Rettori, C.; Fisk, Z.; Oseroff, S. B. (Amer Physical Soc, 2007)
Electron spin resonance of Eu(2+) (4f(7), S=7/2) in a La hexaboride (LaB(6)) single crystal shows a single anisotropic Dysonian resonance. From the observed negative g shift of the resonance, it is inferred that the Eu(2+) ions are covalent exchange coupled to the B 2p-like host conduction electrons. From the anisotropy of the spectra (linewidth and field for resonance), we found that the S ground state of Eu(2+) ions experience a cubic crystal field of a negative fourth order crystal field parameter (CFP), b(4)=-11.5(2.0) Oe, in agreement with the negative fourth order CFP, A(4), found for the non-S ground state R hexaborides. These results support covalency as the dominant contribution to the fourth order CFP for the whole R hexaboride family.